2021
DOI: 10.1002/advs.202004552
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline‐Coated MOFs Nanorod Arrays for Efficient Evaporation‐Driven Electricity Generation and Solar Steam Desalination

Abstract: Though evaporation‐driven electricity generation has emerged as a novel eco‐friendly energy and attracted intense interests, it is typically demonstrated in pure water or a very low salt concentration. Integrating evaporation‐driven electricity generation and solar steam desalination simultaneously should be more promising. Herein, a polyaniline coated metal‐organic frameworks (MOFs) nanorod arrays membrane is synthesized which inherits the merits of both polyaniline and MOFs, demonstrating nice stability, goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 48 publications
0
85
0
Order By: Relevance
“…Therefore, we perform a comparison with recently reported state-of-the-art absorbers in terms of surface temperature and thickness (Figure 6e, Table S3, Supporting Information), demonstrating that both surface temperature and thickness of the proposed absorber are desirable. [7,11,[44][45][46][47][48][49] It is worth to note that not all the surface temperatures of those absorbers are measured at an ambient temperature of 28 C, which may impact the measured results. [50,51]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we perform a comparison with recently reported state-of-the-art absorbers in terms of surface temperature and thickness (Figure 6e, Table S3, Supporting Information), demonstrating that both surface temperature and thickness of the proposed absorber are desirable. [7,11,[44][45][46][47][48][49] It is worth to note that not all the surface temperatures of those absorbers are measured at an ambient temperature of 28 C, which may impact the measured results. [50,51]…”
Section: Resultsmentioning
confidence: 99%
“…One can see the continuous current response when the light was moved from the left region to the center and then to the right region of the MXene membrane, along with reverse current direction. Moreover, Peng et al [174] fabricated a polyanilinecoated MOFs nanorod arrays membrane for electricity generation and seawater desalination by the light-induced water evaporation. These works provide valuable inspirations for further investigation of using nanofluidic photothermal electricity as an alternative solar electricity technology for power generation.…”
Section: Self-responsive Materials Fabricated For the Nanochannelsmentioning
confidence: 99%
“…In 2001, Kral and Shapiro first theoretically predicted that electricity can be generated in metallic carbon nanotubes when water is flowing along them . After that, numerous theoretical and experimental works have shown that low-dimensional carbon-based materials, including carbon nanotubes, graphene, and carbon nanoparticles, have the potential to generate electricity through interactions with water. However, the voltage generated by these generators is normally only tens of microvolts to millivolts without continuous output, which is insufficient to power the current device, hindering their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Zhou et al developed centimeter-sized carbon black sheets, which can reliably generate continuous voltages of up to 1 V under environmental conditions. After that, various carbon black-based generators and applications were booming. Unfortunately, this research field is still at a primary stage, and most of the recent studies focus on carbon-based materials. Only several metal oxides (hydroxides) and semiconductor materials have been demonstrated to show such capability.…”
Section: Introductionmentioning
confidence: 99%